Corporate social responsibility and its effect on image and reputation: The case of L’Oréal and its acquisition of The Body Shop - Koczor, Nathalie (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics